Mechanics analysis on the composite flywheel stacked from circular twill woven fabric rings. (1st November 2016) - Dai, Xingjian; Wang, Yong; Tang, Changliang; Guo, Xingfeng
Abstract: The filament wound composite flywheel had a deficiency of being fragile along the radial direction because there is no reinforcing phase distribution. The failure along the radial direction due to delamination may happen when the thick cylinder composite flywheel rotate at high speed. A new way to solve the low radial strength problem of the composite flywheel is to use woven fabric material. The 2D woven fabric composite in the form of a circular ring has fibers in both the circumferential and radial directions to bear the stress. This structure features the combination of the typical two-dimensional orthogonal textile fabric and the classic axial laminations, performing new characters in mechanics. Samples of composite disks with 2D woven fabric material were designed and fabricated for spinning test, and the mechanics analysis on the thin woven composite disk was carried out for the first time. With the introduction of micromechanics methods, the elastic constants of the unit cell model of periodic volume representing the whole fabric were extracted from geometrical simplification and homogenization theories. The stiffness and strength of orthogonal twill woven fabric were predicted to evaluate the failure spinning speed of the fabric composite disks. The theoretical maximum spin speed of the woven flywheel could reach 1261 rps with energy density of 53 W h/kg. The tension test data on samples of twill woven fabric composite helped with the prediction of failure of disk samples. The spinning tests confirmed that the tail weakness of the stacked configuration and the stiffness degradation from defects in composite contributed greatly to the stable running of flywheel spin.